Computational Study on DNA Repair: The Roles of Electrostatic Interactions Between Uracil-DNA Glycosylase (UDG) and DNA - Xie, Yixin; Karki, Chitra B.; Chen, Jiawei; Liu, Dongfang; Li, Lin (Frontiers in Molecular Biosciences, 2021)
Uracil-DNA glycosylase (UDG) is one of the most important base excision repair (BER) enzymes that is aiming at the repair of uracil-induced DNA lesion by removing uracil from damaged DNA. Uracil in DNA may occur due to the cytosine deamination or deoxy uridine monophosphate (dUMP) residues misincorporation during DNA synthesis. Medical evidences show that an abnormal expression of UDG is related to different types of cancer, including colorectal cancer, lung cancer, liver cancer, etc. Therefore, the research of UDG is crucial in cancer treatment and prevention, as well as other clinical activities. Here we applied multiple computational methods to study the UDG in several perspectives: Understand the stability of UDG enzyme in different pH conditions; study the differences in charge distribution between the pocket side and non-pocket side of UDG; analyze the field line distribution at the interfacial area between UDG and DNA; perform binding force analyses of special region of UDG (pocket area) and target DNA base (uracil); as well as investigate the charged residues on UDG binding pocket and binding interface. Our results show that it is the whole UDG binding interface rather than the UDG pocket area who provides the binding attractive force to the damaged DNA at uracil base.